Effect of crystallinity of zeolite beta on physicochemical properties and performance of cobalt catalysts - Piaw Phatai; Sirinuch Loiha; Sanchai Prayoonpokarach; Jatuporn Wittayakun (Penerbit Universiti Kebangsaan Malaysia, 2020)
In the present work, the effect of crystallinity of zeolite beta in a sodium form (NaBEA) on physicochemical properties and performance of NaBEA-supported cobalt catalysts was investigated. The incipient wetness impregnation method was utilized in the synthesis of NaBEA-supported cobalt catalysts with various Co loadings (4, 7 and 10 wt. %). NaBEA materials with high and low crystallinities (NaBEA-H and NaBEA-L) were synthesized using fumed silica with aging times of 72 and 48 h, respectively. In comparison to NaBEA-L, higher XRD peak intensities and surface area were observed for NaBEA-H. After impregnation, NaBEA-L displayed better dispersion of Co species and lower reducibility than NaBEA-H due to stronger metal-support interaction. Catalytic performance for n-butane hydrogenolysis via Co/NaBEA-H and Co/NaBEA-L catalysts was compared. In butane hydrogenolysis, the higher conversion was attained using Co/NaBEA-H with 7 and 10 wt. % when compared to Co/NaBEA-L with similar loadings. Multiple hydrogenolysis occurred on all catalysts producing methane as the only product. The most effective catalyst was determined to be 7Co/NaBEA-H due to the higher surface area and uniform particles of the cobalt species.